PRIMA 2017 : principles and practice of multi-agent systems : 20th International Conference, Nice, France, October 30-November 3, 2017, Proceedings /: principles and practice of multi-agent systems : 20th International Conference, Nice, France, October 30-November 3, 2017, Proceedings. (2017) - Unknown
No abstract available